The effect of home-based transcranial direct current stimulation in cognitive performance in fibromyalgia: A randomized, double-blind sham-controlled trial - Serrano, Paul Vicuña; Zortea, Maxciel; Alves, Rael Lopes; Beltrán, Gerardo; Bavaresco, Cibely; Ramalho, Leticia; Alves, Camila Fernanda da Silveira; Medeiros, Liciane; Sanches, Paulo R. S.; Silva, Danton P.; Lucena da Silva Torres, Iraci; Fregni, Felipe; et al. (Frontiers in Human Neuroscience, 2022)
Background: Transcranial Direct Current Stimulation (tDCS) is a promising approach to improve fibromyalgia (FM) symptoms, including cognitive impairment. This trial evaluated the efficacy and safety of home-based tDCS in treating cognitive impairment. Besides, we explored if the severity of dysfunction of the Descendant Pain Modulation System (DPMS) predicts the tDCS effect and if its effect is related to neuroplasticity changes as indexed by the brain-derivate-neurotrophic-factor (BDNF). Methods: This randomized, double-blind, parallel, sham-controlled clinical trial, single-center, included 36 women with FM, aged from 30 to 65 years old, assigned 2:1 to receive a-tDCS (n=24) and s-tDCS (n=12). Our primary outcome was executive attention, divided attention, working memory (WM), and cognitive flexibility evaluated by the Trail Making Test (TMT-B-A). We assessed the WM by Digits' subtest from the Wechsler Adult Intelligence Scale (WAIS-III), executive functions (Controlled Oral Word Association Test (COWAT)), and quality of life (secondary outcomes). Intervention: 20-minute daily sessions of home-based tDCS for four weeks (total 20 sessions), 2 mA anodal-left (F3) and cathodal-right (F4) prefrontal stimulation with 35 cm2 carbon electrodes. Results: GLM revealed a main effect for treatment Wald χ2=6.176; Df=1; P=0.03 in the TMT-B-A. The a-tDCS improved cognitive performance. The effect size estimated Cohen’s d at treatment end in the TMT-B-A scores was large [-1.48, confidence interval (CI) 95%= -2.07 to -0.90]. Likewise, the a-tDCS effects compared to s-tDCS improved the performance in the WM, verbal and phonemic fluency, and improved scores on the quality-of-life scale. The impact of a-tDCS on the cognitive tests was positively correlated with the reduction in serum BDNF from baseline to treatment end. Besides, the reduction in the serum BDNF was positively correlated with the improvement in the quality of life due to FM symptoms. Conclusion: These findings revealed that daily treatment with a home-based tDCS device over l-DLPFC compared to sham stimulation over four weeks improved the cognitive impairment in FM. The a-tDCS at home was well-tolerated, underlining its potential as an alternative treatment for cognitive dysfunction. Besides, the a-tDCS effect is related to the severity of DPMS dysfunction and changes in neuroplasticity state.